2022
DOI: 10.3389/fendo.2022.904986
|View full text |Cite
|
Sign up to set email alerts
|

Hürthle Cell Carcinoma: Single Center Analysis and Considerations for Surgical Management Based on the Recent Literature

Abstract: BackgroundHürthle cell carcinoma (HCC) of the thyroid is rare. There are contrasting data on its clinical behavior. The aim of this study was to describe clinic-pathological features and outcomes of HCC patients at our institution, in order to adapt our surgical management.MethodsWe retrospectively studied 51 cases of HCC treated at the interdisciplinary endocrine center of the University Hospital of Cologne, Germany between 2005 and 2020.ResultsPatients median age was 63 years (range 29-78) with 64.7% of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Perhaps not surprisingly, given the historical marginalization of this population, approximately 33% of these veterans presented with at least minimal extrathyroidal extension, which is an increased proportion from previous estimates of approximately 9% [ 34 ]. We also demonstrate a higher proportion of the follicular variant of papillary thyroid carcinoma—18.5% of papillary thyroid carcinomas in our population, compared with 10% to 15% in previous estimates [ 35 ]—and of Hürthle cell carcinoma—11.8% of our population, compared with 3% to 4% of cancers in previous estimates [ 36 , 37 ]. It remains unknown whether these rates will hold on a larger scale if examined among all veterans.…”
Section: Discussionsupporting
confidence: 66%
“…Perhaps not surprisingly, given the historical marginalization of this population, approximately 33% of these veterans presented with at least minimal extrathyroidal extension, which is an increased proportion from previous estimates of approximately 9% [ 34 ]. We also demonstrate a higher proportion of the follicular variant of papillary thyroid carcinoma—18.5% of papillary thyroid carcinomas in our population, compared with 10% to 15% in previous estimates [ 35 ]—and of Hürthle cell carcinoma—11.8% of our population, compared with 3% to 4% of cancers in previous estimates [ 36 , 37 ]. It remains unknown whether these rates will hold on a larger scale if examined among all veterans.…”
Section: Discussionsupporting
confidence: 66%
“…Chiapponi et al reported US data for their OCA cohort of 51 patients, noting 85% had a solid composition, 55% were hypoechoic, and over 90% had smooth borders. 21 Similarly, the majority of OCA nodules in this cohort were solid and hypoechoic. However, a large number were reported as mixed cystic and solid.…”
Section: Discussionmentioning
confidence: 67%
“…The patient population evaluated in this study had a similar age average and range to previous single center and SEERdatabase studies. 18,21 This study population had a slightly higher proportion of males. The most common demographic risk factor appreciated was a family history of thyroid cancer, which was appreciated in nearly a quarter of this cohort.…”
Section: Discussionmentioning
confidence: 90%
“…Although total thyroidectomy facilitates the ability to follow thyroglobulin as a tumor marker, several reports have also suggested that thyroglobulin levels in OTC may be less reliable for monitoring for recurrent disease . Prophylactic central neck dissection has not been shown to improve outcomes . Overall, data quality regarding these important surgical perioperative issues are limited and most studies are retrospective.…”
Section: Observationsmentioning
confidence: 99%